Pengaruh Kepemimpinan Transformasional Kepala Sekolah Dan Motivasi Kerja Terhadap Kinerja Guru SMK Negeri Jakarta Utara - Sugiarto Sugiarto; Wahidin Wahidin; Totok Amin Soefijanto (Tadbir : Jurnal Studi Manajemen Pendidikan, 2020)
Teacher’s performance plays a crucial role in achieving quality of education and good character of students. Low teacher’s performance will decrease quality of graduates itself. Based on data in north Jakarta vocational school, teacher’s performance is in priority programs of government, and still need to be increased. The objectives of this research is to investigate whether there exist any direct positive effect of transformational leadership and work motivation towards teacher’s performance at North Jakarta Vocational School. As many as 81 from 443 teachers were used as research samples to obtain data which were then analyzed using quantitative methods of path analysis. The result shows that there exists a positive direct effect of (1) transformational leadership towards teacher performance, (2) work motivation towards teacher performance, (3) transformational leadership towards work motivation.